Design of A Profile of Needs for Basic Reading Teaching Materials in Riau Province - Mukminati Zulfa; Asnawi Asnawi (Universitas Pendidikan Mandalika (UNDIKMA), 2024)
This research aims to design a profile of needs for basic reading teaching materials, especially at the tertiary level. This study used a descriptive method with a qualitative approach. Research data was collected using a questionnaire. The profile questionnaire for the need for teaching materials for the basics of reading was displayed on the Google form platform. The research data was in the form of questionnaire results distributed based on the needs of students in the Indonesian Language and Literature Education Study Program which was available at 3 leading universities in Riau Province, namely Riau Islamic University, Riau University and Sultan Syarif Kasim Riau State Islamic University. After getting the questionnaire results, data validation was carried out using interviews. Next, the data analysis technique was carried out using reflective techniques with the help of TagCrowd. The results of the research showed that the profile of the need for teaching materials for the basics of reading required by Language and Literature Education Students in Riau Province was based on four factors, namely factors (1) the content needs of students who want to understand the theory of reading skills, of course in accordance with real life and mastery of skills, (2) ) students' linguistic needs want popular vocabulary with complex information using simple sentences to make it easier to understand, (3) students' graphic needs want a book display with Times News Roman letters, 12 and A4 size paper equipped with pictures, audio and video, 21x29 cm using frames, and (4) students' learning media needs require teaching media in the form of printed books/e-books with interactive material containing public facilities such as tourist attractions and entertainment.) in the form of dialogue texts.